Analisis Wacana Kritis Norman Fairclough Pernyataan Megawati: “Pak Jokowi Kalau nggak Ada PDI Perjuangan duh Kasihan dah” - Sandi, Putri Paradilah; ., Mayasari; Yusup, Eka (CV. ITTC INDONESIA, 2024)
Partai Demokrasi Indonesia Perjuangan (PDIP) held its 50th Anniversary celebration on January 10, 2023. During the celebration, Megawati as the Chairperson of the party mentioned,